Connecting the Micro to the Macro: An Exploration of Micro-Behaviors of Individuals Who Drive CSR Initiatives at the Macro-Level - Poonamallee, Latha; Joy, Simy (Frontiers in Psychology, 2018)
This paper presents an integrated CSR model that combines individual CSR actions with organizational CSR model. Individual CSR actions have been identified based on a case study of the formation of a successful inter-organizational CSR partnership in India that addresses livelihoods and education needs of the at-risk vulnerable youth. These micro-actions include identifying opportunities, assuming personal responsibility for action, leveraging personal skills, leveraging personal networks, and leveraging organizational resources.